The Glasgow miracle? Storytelling, violence reduction and public policy - Fraser, Alistair David (Theoretical criminology, 2024)
The city of Glasgow, once dubbed the ‘murder capital of Europe’, has more recently become famed for its experiments in violence reduction. In this article, based on a large-scale study of violence reduction, we focus on the discursive construction of this so-called ‘Glasgow miracle’. Based on interviews with 40 senior stakeholders working in Scotland during the period 2000–2020, we explore the significance of dramatic personal stories of tragedy, redemption, and rebirth in shifting the public narrative around violence. In so doing, we contribute new empirical and theoretical evidence to narrative criminology, demonstrate the conditions under which progressive policies can come to the fore, and interrogate the role of storytellers in communicating these stories with persuasion and influence.